Beyond the clinic: how the physical therapist can contribute to the social struggles of people with disabilities in Brazil (Research, Society and Development, 2022)
The physiotherapist, a health professional who works directly in the care of people with disabilities, could help in the fight against the various oppressions suffered by people with disabilities. The objective of the study was to discuss about how the physical therapist can contribute to the social struggles of people with disabilities in the country. Such a professional should be encouraged to question the system. It is a profession that has a social locus seen as superior in relation to people with disabilities. By understanding how our profession also reproduces capableist ideas and how our actions directly affect the social life of people with disabilities, we can then understand the disabled person as a member of society that must have their rights as citizens preserved and that we must help in their struggles against an oppressive society.